Patients' understanding of diabetes self-management education and support in a private primary care clinic in Kuala Lumpur: A qualitative study / Tharini Thanapalan - Tharini, Thanapalan (2020)
Patients with diabetes mellitus should be actively self-managing their disease, since this can aid in producing better glycaemic control. Thus healthcare professionals managing diabetes patients, irrespective of whether they are in the public or private setting, need to focus on educating patients in order to empower them to carry out self-management practices. Little evidence is available to determine whether patients, especially those managed in private primary care clinics, are able to understand the education provided to them on diabetes self-management. This study aimed to explore patients’ comprehension of content and perception regarding delivery and quality of diabetes self-management education at a private primary care clinic in Kuala Lumpur, Malaysia. Qualitative in-depth interviews were carried out via Zoom with 21 diabetes mellitus patients being followed-up for at least 6 months at the chosen private primary clinic. Most respondents felt overwhelmed with the information given during the DSME, were mostly satisfied with quality of the delivery of DSME but not so with the deliverer of the DSME, and majority of the respondents felt that the instructional delivery of DSME did not influence either their self-efficacious behaviour nor their health literacy. Patients being followed-up in a private primary care clinic seem to have shortcomings in comprehending DSME, with further research and interventions necessary to improve patient outcomes in the Malaysian setting.